PORTOFOLIO SEBAGAI PENILAIAN ALTERNATIF DI MASA PANDEMI COVID-19 DI MI SE KABUPATEN WAY KANAN - Muhammad Supriyanto (Jurnal Al-Hikmah, 2020)
Abstract The purpose of this study to determine students' perceptions about online lectures process, to find out the forms of application used in online lectures and to find out the supporting factors and resistors factors in online lectures. This research was conducted by descriptive survey research methods, the 4th semester PIAUD students of IAIN Kendari as the sample of this study. The techique of data collection using interviews and questionnaires. This study find 53 or 88.3% from 60 students who answer at home, as many as 2 students or 3.3% who answer in the garden and as many as 5 students or 8.3% who answer family or neighbor's house with a good internet network. Students using electronic devices to attend online lectures are smartphones and laptops. Applications that are preferred in online lectures, as many as 56 students or 91.8% of students use the Whatsapp group application, 4 students or 6.5% of students use the zoom application and 1 student or 1.6% of students use the email application. When asked to students the extent to which the material delivered through online lectures can be understood by 1 student answers very well understood, 23 students answered understood, 34 students answered sometimes understood and as many as 4 students became non-understood. Students as a whole or 100% choose face-to-face lectures compared to online lectures. Keywords: Portfolio, Covid